The Flow-Clutch Scale: Translation and validation study of the Chinese version. (November 2022) - Kuang, Jin; Zhu, Weijia; Herold, Fabian; Chen, Erle; Gerber, Markus; Ludyga, Sebastian; Zhang, Liwei; Müller, Notger G.; Kramer, Arthur F.; Zou, Liye
Abstract: Purpose: The integrated model of flow and clutch provides a multistate perspective to the optimal experiences during physical exercises. Based on this model, the Flow-Clutch Scale (FCS) was developed. The current study is the first step to test the psychometric properties of a Chinese version of the FCS (FCS–C). Method: A confirmatory factor analysis (CFA) with Maximum Likelihood estimate was performed in Chinese athletes ( N  = 426) to explore the structural validity of the FCS-C . The Pearson correlations between the subscales of the FCS-C and "non-reactivity to inner experiences", "cognitive flexibility", and "self-consciousness" were explored to examine the concurrent validity. Cronbach's alpha coefficients were used to assess the internal consistency of the total scale and subscales. Moreover, the test-retest reliability was examined in a subsample ( N  = 53) using a two-week interval. Results: The results of CFA suggested that the three-factor model showed an acceptable model fit (χ 2  = 459.40, df  = 120, CFI = 0.95, GFI = 0.90, SRMR = 0.03, RMSEA = 0.082 [90% CI = 0.074–0.09]). Concerning the correlations between the factor "characteristics of flow" and "self-consciousness", the concurrent validity was not satisfactory. Moreover, the test-retest coefficients ranged from 0.75 to 0.78 ( p  < .01) and Cronbach's alpha ranged from 0.87 to 0.96. Conclusion: Results indicated that the three-factor model of FCS-C is acceptable, whereas its validity is not satisfactory to appropriately examine flow and/or clutch states in Chinese athletes. In summary, the current translation and validation study of the FCS-C allows for future research on optimal exercise experiences in Chinese-speaking cohorts including a further cultural adaptation of the questionnaire.